Cosmopolitan aesthetics art in a global world - Herwitz, Daniel Alan 1955- (Bloomsbury Academic, 2020)
New social realities and changes in contemporary art are impacting our traditional ideas about aesthetics. Art, art markets and aesthetics now interact in ways that demand new forms of thought. 'Cosmopolitan Aesthetics' presents the first thorough account of the challenges facing aesthetics today, introducing the history that underpins them. This is an ideal starting point for anyone looking to better understand 21st century aesthetics and art. Not only does Daniel Herwitz show how aesthetics was born as a series of philosophical positions on taste, beauty and the sublime, he explains what a global world means for aesthetics
Keywords: Ästhetik; Globalisierung; Kunst; Aesthetics, Modern / 21st century; Art, Modern / 21st century; Aesthetics, Modern; Art, Modern; 2000-2099